PERILAKU AMAN PADA PEKERJA OPERATOR LOADING UNLOADING MINYAK MENTAH - Feby Cahyani (Universitas Airlangga, 2018)
Elements that play an important role in the cause of occupational accidents are human behavior. Thus reducing the occurrence of unsafe behavior is an effective way to prevent the occurrence of work accidents. From the results of preliminary studies conducted in the production area of PT X from 10 workers who observed the behavior of the use of PPE there were 3 workers who did not behave safely. This study aims to analyze the safe behavior and its causes in the effort of prevention of work accident by using Antecedence, Behaviour and Consequences (ABC) behavior model. This research used cross-sectional design. Data collection was obtained through measurement and observation. The population of this research was 20 workers loading unloading crude oil. The result of the research showed that 50% of workers doing the safe behavior. The safe behavior of the use of PPE by 80%, the implementation of housekeeping by 70%, and follow the Standard Operating Procedure (SOP) of 83%. Safe behavior was triggered by the important role of knowledge that workers have good enough about Occupational Health and Safety (OHS) and safe behavior, worker attitudes toward safe behavior also quite good, and the training received is good enough. Besides giving rewards and punishment by the company also helped motivate workers to behave safely. While unsafe behavior that workers do not use a respirator and does not maintain the cleanliness of the workplace.Keywords: ABC model, loading unloading operator, safe behavior